Preparation method of long-acting operation catalyst for methanol synthesis
The copper-zinc-aluminum mixed precipitate was prepared by the precipitation method and the introduction of modified graphene and lanthanum chloride were solved, which solved the problems of low activity and poor heat resistance of the existing catalysts, and achieved the preparation of catalysts with high activity, high selectivity and good heat resistance.
Patent Information
- Application Number
- CN202411772447.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The existing methanol synthesis catalysts have low catalytic activity and poor heat resistance, resulting in a decrease in catalytic activity and a short service life.
The copper-zinc-aluminum mixed precipitate is prepared by precipitation method, and modified graphene and lanthanum chloride are introduced during the preparation process to control the growth of metal oxide particles and dispersion of active metals, and improve the synergistic effect of Cu-ZnO and the thermal stability of the catalyst.
It significantly improves the activity, selectivity and thermal stability of the catalyst, extends the service life of the catalyst, and improves the efficiency of methanol synthesis.
Smart Images

Figure BDA0005170577700000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for preparing a long-acting operating catalyst for methanol synthesis. Background Art
[0002] Methanol (CH3OH) is an important basic organic chemical raw material. It can be used to manufacture a variety of organic products such as methyl chloride, methylamine and dimethyl sulfate. It is also a raw material for pesticides (insecticides, acaricides), medicines (sulfonamides, synmycin, etc.), and the main raw material for the synthesis of dimethyl terephthalate, methyl methacrylate and methyl acrylate. It is widely used in organic synthesis, dyes, medicines, pesticides, coatings, automobiles and defense industries. In industry, methanol is generally produced by the synthesis gas of H2, CO, CO2 prepared from natural gas, coke oven gas or coal, etc., under certain pressure and temperature conditions, through the action of a catalyst.
[0003] At present, the catalyst used for synthesizing methanol is basically a copper-zinc-aluminum catalyst. The three components of CuO, ZnO and Al2O3 in the catalyst for synthesizing methanol have different functions. CuO is the main active component, and ZnO and Al2O3 are additives. The addition of ZnO can make the catalyst form a Cu / Zn synergist, which greatly improves the activity and selectivity of the catalyst. Al2O3 not only plays a skeleton role in the catalyst, but also can disperse the active components in the catalyst, so that the adsorption and conversion rate of CO2 can be improved. Adding an appropriate amount of Al2O3 to the copper-based catalyst can improve the selectivity of the catalyst for CO2 hydrogenation to synthesize methanol. Although the copper-zinc-aluminum catalyst has good industrial application effect, it still faces the problem of poor heat resistance: agglomeration and sintering of the active component copper particles and the resulting decrease in catalytic activity; the catalytic activity, selectivity and service life of the catalyst used for industrial methanol synthesis are poor. In the study, it was found that different preparation processes will significantly affect the structure of the catalyst precursor species and the product phase composition of the catalyst, and then affect the activity and stability of the final catalyst. The Chinese patent application document with patent application number CN 1660490A discloses a method for preparing a synthetic methanol catalyst, in which a small amount of surfactant OP is added during the coprecipitation preparation process. The Chinese patent application document with patent application number CN101733109A discloses a method for preparing a copper-based methanol synthesis catalyst, in which an auxiliary agent (one or more of ethylene glycol, diethylamine, glycerol, magnesium stearate, and activated carbon) is added during the precipitation process. The above methods all use organic reagents to improve the Cu-ZnO synergistic effect during the precipitation process, but there are still limitations in improving the dispersion of catalyst metals by organic reagents alone, and the Cu-ZnO synergistic effect is not significantly improved.
[0004] Therefore, developing a methanol synthesis catalyst with better catalytic activity and stability is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a long-acting catalyst for methanol synthesis, so as to solve the problem of low catalytic activity of the methanol synthesis catalyst in the prior art.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a long-acting catalyst for methanol synthesis comprises the following steps:
[0008] Step 1, adding graphene to deionized water, stirring for 22-24 hours, adjusting the pH value to 1.0-1.5, adding LaCl3·6H2O solution, heating to 60-65°C for reaction for 2-3 hours, adjusting the pH value to 2.0-2.5, adding anionic surfactant, continuing the reaction for 2 hours, centrifuging, washing, vacuum drying and grinding to obtain modified graphene;
[0009] Step 2, adding copper nitrate solution, zinc nitrate solution and aluminum nitrate solution into deionized water, heating to 75-80° C., stirring and mixing, adding a precipitant, adjusting the pH value, performing a coprecipitation reaction, filtering, washing and drying to obtain a precipitate;
[0010] Step 3: After the precipitate and the modified graphene are evenly mixed, the mixture is placed in a muffle furnace under air atmosphere for calcination, tableting, and grinding to obtain a catalyst.
[0011] As a further scheme of the present invention, in step 1, the usage ratio of graphene, deionized water, LaCl3·6H2O solution and anionic surfactant is 1.25-1.30 g:50 mL:0.10-0.15 mL:0.30-0.45 mL; wherein the concentration of LaCl3·6H2O solution is 0.4-0.5 mol / L.
[0012] As a further embodiment of the present invention, the anionic surfactant in step 1 is one of sodium monododecyl phosphate, sodium dodecyl sulfonate and sodium dodecyl carboxylate.
[0013] As a further embodiment of the present invention, in step 2, the usage ratio of the copper nitrate solution, the zinc nitrate solution, the aluminum nitrate solution, the deionized water and the precipitant is 25-28 g: 5-8 g: 3-5 g: 100 mL: 18-20 g.
[0014] As a further embodiment of the present invention, the concentration of the copper nitrate solution in step 2 is 2.0-4.0 mol / L in terms of copper ions, the concentration of the zinc nitrate solution is 2.0-4.0 mol / L in terms of zinc ions, and the concentration of the aluminum nitrate solution is 1.0-3.5 mol / L in terms of aluminum ions.
[0015] As a further embodiment of the present invention, the precipitant in step 2 is one of sodium carbonate, potassium carbonate and ammonium carbonate.
[0016] As a further solution of the present invention, the pH value in step 2 is adjusted to 7.5-8.5.
[0017] As a further solution of the present invention, the amount of modified graphene in step 3 is 3%-5% of the mass of the precipitate.
[0018] As a further solution of the present invention, in step 3, the calcination temperature is 350-400° C., the heating rate is 2-3° C. / min, and the calcination time is 10-12 h.
[0019] As a further solution of the present invention, in step 3, the powder is ground to a particle size of 60-100 mesh.
[0020] Beneficial effects of the present invention:
[0021] The method of the present invention uses a precipitation method, firstly, a mixture containing part of Cu, Zn and Al is subjected to a coprecipitation reaction to prepare a copper-zinc-aluminum mixed precipitate; by regulating the preparation steps and preparation conditions, in the process of the growth of the copper, zinc and aluminum mixed precipitate particles, different active metals are deposited in the catalyst in an orderly manner, the growth rate of the metal oxide particles and the probability of contact between the active metals are controlled, the dispersion of copper is improved, the Cu-ZnO synergy is increased, the active center is greatly improved, and the Al2O3 generated by the precipitation of the aluminum source has a good skeleton effect, so that the main active component copper and the auxiliary agent zinc are dispersed more evenly, which is conducive to the improvement of catalyst activity, methanol selectivity and thermal stability. Further, in the present invention, lanthanum chloride and anionic surfactants are used to intercalate and modify graphene, effectively increase the spacing between graphene layers, and improve its dispersion performance and thermal stability performance; and then the modified graphene is introduced into the copper-zinc-aluminum catalyst to greatly improve the thermal stability and heat resistance of the copper-zinc-aluminum catalyst. In addition, the introduction of rare metal lanthanum inhibits the sintering of copper particles, avoids the agglomeration of copper particles, improves the stability of the copper-zinc-aluminum catalyst, and further maintains the activity of the copper-zinc-aluminum catalyst. At the same time, it helps to increase the specific surface area of copper and the number of basic sites, which is conducive to the formation of methanol and improves the selectivity of methanol synthesis.
[0022] The invention provides a method for preparing a long-acting catalyst for methanol synthesis, which has a simple process, economical cost and is suitable for large-scale production. The prepared catalyst has high activity, high selectivity and good heat resistance. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] This embodiment provides a method for preparing a long-term operation catalyst for methanol synthesis, comprising the following steps:
[0026] Step 1: Add 1.25 g of graphene to 50 mL of deionized water, stir for 24 h, adjust the pH value to 1.0, add 0.10 mL of LaCl3·6H2O solution (0.4 mol / L), heat to 60 °C and react for 2 h, adjust the pH value to 2.0, add 0.30 mL of sodium dodecyl sulfate, continue to react for 2 h, centrifuge, wash with hot deionized water, identify Cl by 0.1 mol / L AgNO3 - Whether it is completely washed off, it is then washed three times with 50% ethanol, vacuum dried, and ground to obtain modified graphene;
[0027] Step 2, add 25g of copper nitrate solution, 5g of zinc nitrate solution and 3g of aluminum nitrate solution into 100mL of deionized water, heat to 80°C and stir to mix, add 18g of sodium carbonate, adjust the pH value to 7.5 for coprecipitation reaction, filter, wash and dry to obtain a precipitate;
[0028] Step 3: After evenly mixing 100 g of the precipitate and 3 g of the modified graphene, the mixture was placed in a muffle furnace for calcination under air atmosphere at a temperature of 300 ° C., a heating rate of 2 ° C / min, and a calcination time of 10 h. The mixture was pressed into tablets and ground into a particle size of 60 mesh to obtain a catalyst.
[0029] Example 2
[0030] Compared with Example 1, the only difference is:
[0031] Step 1: Add 1.30 g of graphene to 50 mL of deionized water, stir for 24 h, adjust the pH value to 1.0, add 0.15 mL of LaCl3·6H2O solution (0.4 mol / L), heat to 60 °C and react for 2 h, adjust the pH value to 2.0, add 0.45 mL of sodium dodecyl sulfate, continue to react for 2 h, centrifuge, wash with hot deionized water, identify Cl by 0.1 mol / L AgNO3 - To determine whether the graphene was completely washed off, the graphene was washed three times with 50% ethanol, and then vacuum dried and ground to obtain the modified graphene.
[0032] Example 3
[0033] Compared with Example 1, the only difference is:
[0034] Step 2: Add 26 g of copper nitrate solution, 6 g of zinc nitrate solution and 3.5 g of aluminum nitrate solution into 100 mL of deionized water, heat to 80° C. and stir to mix, add 18 g of sodium carbonate, adjust the pH value to 7.5 for coprecipitation reaction, filter, wash and dry to obtain a precipitate.
[0035] Example 4
[0036] Compared with Example 1, the only difference is:
[0037] Step 2: Add 27.5 g of copper nitrate solution, 7.8 g of zinc nitrate solution and 4.5 g of aluminum nitrate solution into 100 mL of deionized water, heat to 80° C. and stir to mix, add 19.5 g of sodium carbonate, adjust the pH value to 8.5 for coprecipitation reaction, filter, wash and dry to obtain a precipitate.
[0038] Example 5
[0039] Compared with Example 1, the only difference is:
[0040] Step 3: After evenly mixing 100 g of the precipitate and 3 g of the modified graphene, the mixture was placed in a muffle furnace for calcination under air atmosphere at a temperature of 390°C, a heating rate of 2.5°C / min, and a calcination time of 12 h. The mixture was pressed into tablets and ground to a particle size of 60 mesh to obtain a catalyst.
[0041] Comparative Example 1
[0042] This comparative example provides a method for preparing a long-acting catalyst for methanol synthesis, comprising the following steps:
[0043] Step 1, add 25g of copper nitrate solution, 5g of zinc nitrate solution and 3g of aluminum nitrate solution into 100mL of deionized water, heat to 80°C and stir to mix, add 18g of sodium carbonate, adjust the pH value to 7.5 for coprecipitation reaction, filter, wash and dry to obtain a precipitate;
[0044] Step 3: calcine 100 g of the precipitate in a muffle furnace under air atmosphere at a temperature of 300° C., a heating rate of 2° C. / min, and a calcination time of 10 h. Press the mixture into tablets and grind it to a particle size of 60 mesh to obtain a catalyst.
[0045] Comparative Example 2
[0046] Compared with Example 1, the only difference is:
[0047] Step 2: Add 20 g of copper nitrate solution, 5 g of zinc nitrate solution and 3 g of aluminum nitrate solution into 100 mL of deionized water, heat to 80° C., stir and mix, add 18 g of sodium carbonate, adjust the pH value to 7.5 for coprecipitation reaction, filter, wash and dry to obtain a precipitate.
[0048] Comparative Example 3
[0049] Compared with Example 1, the only difference is:
[0050] Step 3: After evenly mixing 100 g of the precipitate and 1.5 g of the modified graphene, the mixture was placed in a muffle furnace for calcination under air atmosphere at a temperature of 300 ° C., a heating rate of 2 ° C / min, and a calcination time of 10 h. The mixture was pressed into tablets and ground to a particle size of 60 mesh to obtain a catalyst.
[0051] Comparative Example 4
[0052] Compared with Example 1, the only difference is:
[0053] Step 3: After evenly mixing 100 g of the precipitate and 6 g of the modified graphene, the mixture was placed in a muffle furnace for calcination under air atmosphere at a temperature of 300 ° C., a heating rate of 2 ° C / min, and a calcination time of 10 h. The mixture was pressed into tablets and ground to a particle size of 60 mesh to obtain a catalyst.
[0054] The catalytic performance of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested:
[0055] The catalysts obtained in the examples and comparative examples were respectively subjected to reduction treatment in a H2 / N2 mixed gas containing 5% H2, and then heated in a reaction atmosphere of CO, CO2, H2 and N2 at a space velocity of 10000 h -1 The methanol synthesis catalytic reaction was carried out under the conditions of 4.0 MPa, 4.0 MPa pressure and 250°C reaction temperature, and the methanol yield obtained was taken as the initial activity of the catalyst. After the sample was subjected to heat shock treatment (heat treatment for 5 h under reaction atmosphere, normal pressure and 400°C), it was restored to the above-mentioned activity evaluation conditions, and the measured activity result was the activity after heat resistance; the above-mentioned measurement results are shown in Table 1:
[0056] Table 1
[0057]
[0058] It can be seen from Table 1 that, compared with Comparative Examples 1-4, the catalyst activity, activity stability and methanol selectivity of the catalysts obtained in Examples 1-5 are more excellent. It can be seen that the doping of modified graphene in the process of preparing the catalyst and the parameter limitation in the process of preparing the catalyst in the present invention will affect the activity, activity stability and methanol selectivity of the catalyst. The catalyst prepared by the preparation method of a long-acting catalyst for methanol synthesis provided by the present invention has good catalytic performance and heat resistance, low activity decay rate and excellent methanol selectivity; at the same time, the preparation method is simple, cost-effective, and suitable for large-scale production.
[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a long-acting catalyst for methanol synthesis, characterized in that: The following steps are involved: Step 1, adding graphene to deionized water, stirring for 22-24 hours, adjusting the pH value to 1.0-1.5, adding LaCl3·6H2O solution, heating to 60-65°C for reaction for 2-3 hours, adjusting the pH value to 2.0-2.5, adding anionic surfactant, continuing the reaction for 2 hours, centrifuging, washing, vacuum drying and grinding to obtain modified graphene; Step 2, adding copper nitrate solution, zinc nitrate solution and aluminum nitrate solution into deionized water, heating to 75-80° C., stirring and mixing, adding a precipitant, adjusting the pH value, performing a coprecipitation reaction, filtering, washing and drying to obtain a precipitate; Step 3: After the precipitate and the modified graphene are evenly mixed, the mixture is placed in a muffle furnace under air atmosphere for calcination, tableting, and grinding to obtain a catalyst.
2. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: In step 1, the usage ratio of graphene, deionized water, LaCl3·6H2O solution and anionic surfactant is 1.25-1.30 g:50 mL:0.10-0.15 mL:0.30-0.45 mL; wherein the concentration of LaCl3·6H2O solution is 0.4-0.5 mol / L.
3. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: The anionic surfactant in step 1 is one of sodium monododecyl phosphate, sodium dodecyl sulfonate and sodium dodecyl carboxylate.
4. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: In step 2, the usage ratio of the copper nitrate solution, the zinc nitrate solution, the aluminum nitrate solution, the deionized water and the precipitant is 25-28 g: 5-8 g: 3-5 g: 100 mL: 18-20 g.
5. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: The concentration of the copper nitrate solution in step 2 is 2.0-4.0 mol / L in terms of copper ions, the concentration of the zinc nitrate solution is 2.0-4.0 mol / L in terms of zinc ions, and the concentration of the aluminum nitrate solution is 1.0-3.5 mol / L in terms of aluminum ions.
6. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: The precipitating agent in step 2 is one of sodium carbonate, potassium carbonate and ammonium carbonate.
7. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: In step 2, the pH value is adjusted to 7.5-8.
5.
8. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: The amount of modified graphene used in step 3 is 3%-5% of the mass of the precipitate.
9. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: In step 3, the calcination temperature is 350-400°C, the heating rate is 2-3°C / min, and the calcination time is 10-12h.
10. The method for preparing a long-acting catalyst for methanol synthesis according to claim 1, characterized in that: In step 3, the powder is ground to a particle size of 60-100 mesh.
Citation Information
Patent Citations
Preparation method of copper-based catalyst
CN101733109A
Preparation method of synthesizing catalyst of methyl alcohol
CN1660490A
Cited By
Carbon-doped CZA catalyst with high catalytic performance, preparation method of carbon-doped CZA catalyst and application of carbon-doped CZA catalyst in preparation of methanol by catalyzing CO2 hydrogenation
CN121178171A